Global innovation index 2019 Creating Healthy Lives - The Future of Medical Innovation (WIPO, 2019)
The Global Innovation Index 2019 provides detailed metrics about the innovation performance of 129 countries and economies around the world. Its 80 indicators explore a broad vision of innovation, including political environment, education, infrastructure and business sophistication. The GII 2019 analyzes the medical innovation landscape of the next decade, looking at how technological and non-technological medical innovation will transform the delivery of healthcare worldwide. It also explores the role and dynamics of medical innovation as it shapes the future of healthcare, and the potential influence this may have on economic growth. Chapters of the report provide more details on this year’s theme from academic, business, and particular country perspectives from leading experts and decision makers. El Índice de Innovación Global 2019 proporciona métricas detalladas sobre el desempeño de la innovación de 129 países y economías de todo el mundo. Sus 80 indicadores exploran una visión amplia de la innovación, incluido el entorno político, la educación, la infraestructura y la sofisticación empresarial. El GII 2019 analiza el panorama de la innovación médica de la próxima década, observando cómo la innovación médica tecnológica y no tecnológica transformará la prestación de atención médica en todo el mundo. También explora el papel y la dinámica de la innovación médica a medida que da forma al futuro de la atención médica y la influencia potencial que esto puede tener en el crecimiento económico. Los capítulos del informe brindan más detalles sobre el tema de este año desde la perspectiva académica, comercial y de un país en particular de los principales expertos y tomadores de decisiones.